Unrecorded Idiomatic Expressions of Sikka Krowe Dialect In Flores Island East-Nusa Tenggara - Darmawan Labira; Maria Nelciana Mua Koban; Rikardus Nasa (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
The  aim  of  this  study  is  to  identify  types  of  idioms  found  in  Sikka Krowe dialect  in Nita sub district of Sikka regency.  The data were taken through interviews and observations. Qualitative method was used in analyzing the data.  As the result, the type of Idiomatic expressions was found.  Those idiomatic expressions are divided into two types; they are classified base on the closeness of the elements and base on the elements of formulation. There are 9 full idioms and 6 partial idioms in the closeness of the elements classification and 10 idioms with part of body: 4 idioms with the word senses, 2 idioms with color; 1 idiom with the names of object name; 4 idiom with animal name; 1 idiom with lant parts, 2 Idiom numeralia, 1 idiom of verba, 1 idiom of nouns, 1 idiom of adjectives.  Meanwhile, the meaning of idiomatic expressions was based on the context of the dialogues and the narratives in Sikka Krowe dialect in Nita sub district of Sikka regency.